Relationship between intrauterine contraceptive devices (IUCD) practice with knowledge and belief among women attending family planning clinic in Jempol Felda scheme Negeri Sembilan , 1995. - Norizah Mokhtar,; Khalib Latip, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A total of 131 women attending family planning clinic at Felda Jempol were sampled to determine the prevalence of intrauterine contraceptive device practise, factors influencing it from the socioeconomic, knowledge and belief aspects. Data was collected using self administered questionaires. Majority of respondents (96.9%) were Malays and had education up to primary level (50%). Only 18.3% used intrauterine contraceptive devices. There was no significant difference by age, spacing, number of children and education level between those who practiced intrauterine contraceptive devices and those who did not. The main source of information was the health service system. Knowledge and belief significantly influenced their practice (p<0.05). There was no significant difference as regards to religion and culture between those who practice and those who did not practice the device.